How Do You Measure a “Technological Revolution”? - Corrado, Carol A; Hulten, Charles R (American Economic Review, 2010)
It is hardly news that we are in the midst of rapid economic change. The advances in information and communication technology (ICT), in the life and other sciences and their profusion of innovative products from the newest electronic devices to the latest drugs and treatments are ample evidence. Equally pervasive are new business models in services (big box retail, online banking, on-demand media) and the explosion in social networking and new business practices ushered in by the Internet (telework, virtual meetings, job boards). Given the magnitude of the changes brought on by these innovations, it is useful to step back and ask: What does economic analysis have to say about the sources and mechanisms of these shifts and revolutions, and what economic metrics are available to measure their overall size and impact? The received theory of economic growth is the natural candidate for this job. It came of age in the 1950s and 1960s with the neoclassical models and emergence of aggregate growth accounting. The latter has become the work horse of empirical macroeconomic growth analysis and the basis for official productivity statistics put out by the Bureau of Labor Statistics (BLS) since 1983. A technological revolution appears, in this framework, as an increase in the fruits of innovation, as measured by the shift in an aggregate production function (termed multifactor